2019
DOI: 10.1002/iub.2132
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐LC based proteomic approach identifies that E6AP interacts with ENO1 and targets it for degradation in breast cancer cells

Abstract: E6AP (E6 associated protein) is a HECT domain containing protein having dual E3 ligase and ERα coactivation activity in breast cancer cells. Although E6AP is known to possess antitumorigenic activity, the underlying molecular mechanism is poorly understood. In the present study, we applied nano-LC based proteomics approach to identify E6AP-interacting proteins where we performed GST-pull down using GST-E6AP from whole cell extracts of MCF7 cells, resolved the differentially interacting proteins on 1D-SDS-PAGE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Up-regulated ENO1can promote various types of human cancer, such as bladder cancer cells, oral squamous cell carcinoma, and breast cancer, by regulating β-catenin [12][13][14][15][16][17][18][19][30][31][32][33]. However, the mechanism of ENO1 regulating proliferation and cell cycle in the HCC remains unknown.Recent studies have shown that ENO1 interacts with a diverse range of proteins and plays a key role in regulating the occurrence and progression of various diseases [29,34,35]. However, there is no report on ENO1-interacting proteins regulating the proliferation and cell cycle of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulated ENO1can promote various types of human cancer, such as bladder cancer cells, oral squamous cell carcinoma, and breast cancer, by regulating β-catenin [12][13][14][15][16][17][18][19][30][31][32][33]. However, the mechanism of ENO1 regulating proliferation and cell cycle in the HCC remains unknown.Recent studies have shown that ENO1 interacts with a diverse range of proteins and plays a key role in regulating the occurrence and progression of various diseases [29,34,35]. However, there is no report on ENO1-interacting proteins regulating the proliferation and cell cycle of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…E6AP ubiquitinates and degrades AIB1 in breast cancer cell lines [ 62 ]. E6AP also ubiquitinates and degrades Enolase1 (ENO1), a glycolytic enzyme [ 63 ]. ENO1 expression is increased in breast cancer [ 64 ], which is likely to play a role in cancer-specific alterations in energy metabolism, i.e., Warburg effects, and also in metastasis via enzymatic degradation of extracellular matrix [ 65 , 66 ].…”
Section: E6ap In Cancermentioning
confidence: 99%
“…E6AP ubiquitinates and degrades AIB1 in breast cancer cell lines [62]. E6AP also ubiquitinates and degrades Enolase1 (ENO1), a glycolytic enzyme [63].…”
Section: Breast Cancermentioning
confidence: 99%